Natural head posture changes after maxillomandibular procedures - A prospective study - Thenmozhi Thirumavalavan; T Selvakumar; M Shanmuga Sundaram; T Guru Prasad; V B Krishna Kumar Raja (Wolters Kluwer Medknow Publications, 2019)
Purpose of the Study: The aim of this study is to evaluate the natural head posture changes in the individuals after orthognathic surgery assessed using cone-beam computed tomography (CBCT) scan. Materials and Methods: The study was conducted in the age group above 18 years who underwent mandibular advancement for the correction of the skeletal deformity. The difference was evaluated in cases with the help of CBCT scan which was taken preoperatively and 3 months postoperatively. The inclusion criteria were patients undergoing mandibular advancement with or without maxillary procedures. The CBCT scan was taken in a natural head position with lips in a relaxed position and without any other tongue movements like swallowing. The exclusion criteria include patients with pharyngeal pathology, syndromic conditions, and history of orthognathic surgery. The head posture was determined by measuring the craniocervical angle (CCA) before and after surgery to evaluate the changes. The study was divided among bilateral sagittal split osteotomy (BSSO) advancement cases and maxillomandibular procedures. The statistical analysis was done using a paired t-test. Results: The head posture changes present in mandibular advancement cases show a decrease in the angulation of CCA in both types. The P value of head posture in BSSO advancement cases was 0.25, and for maxillomandibular cases, it was 0.007. Conclusion: The study was concluded by showing a decrease in the angulation of the CCA after orthognathic surgery. This shows improvement in the facial profile and structural positions.